2023
DOI: 10.1039/d3dt00325f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancement in quantum dot-based materials for energy storage applications: a review

Abstract: The need for energy storage and conversion is growing as a result of the worsening consequences of climate change and the depletion of fossil fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated that integrating QDs with other advanced nanomaterials to develop hybrid nanocomposites can lead to improvements in the untapped performance of QDs as well as the introduction of novel properties (Anil Kumar et al, 2023;Das & Ganguly, 2023). It has been reported that metallic NPs (Mansur et al, 2023), gold NPs (Shao et al, 2023), silver NPs (Gao et al, 2015), and MOF (Haotian Du et al, 2023) were successfully combined with QDs for different application requirements.…”
Section: Qd-based Nanocompositesmentioning
confidence: 99%
“…Some studies have demonstrated that integrating QDs with other advanced nanomaterials to develop hybrid nanocomposites can lead to improvements in the untapped performance of QDs as well as the introduction of novel properties (Anil Kumar et al, 2023;Das & Ganguly, 2023). It has been reported that metallic NPs (Mansur et al, 2023), gold NPs (Shao et al, 2023), silver NPs (Gao et al, 2015), and MOF (Haotian Du et al, 2023) were successfully combined with QDs for different application requirements.…”
Section: Qd-based Nanocompositesmentioning
confidence: 99%